(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the outcome and complications of mini PCNL in the treatment of renal calculi. Study Design: This is a cross sectional study. Place and Duration of Study: This study was conducted at the Department of Urology in Shaikh Zayed Hospital, Lahore from September, 2019 to March, 2020. Materials and Methods: A total 60 cases were included in this study after the approval of the study protocol from hospital ethical committee. All the patients presenting in the Department of Urology, Shaikh Zayed Hospital, fulfilling the inclusion criteria, will be included in the study after explaining and taking fully informed written consent. The mini-PCNL procedure was performed under general anesthesia. Post-operative complications and. Outcomes (Stone Clearance, fall in Hemoglobin and Hospital stay) were noted which has been mentioned in the operational definition. Results: Age distribution of the patients was done, it showed that 68.3% (n=41) patients were in age group of 18-40 years and 31.7%(n=19) in age of 41-60 years and mean age was 36.28±9.73 years. There were 46.7% (n=28) were male and 53.3%(n=32) were female. Stone clearance was in 85% (n=51) patients. Complications were present in 15% (n=9) patients. Conclusion: We concluded that mini PCNL technique is good in stone clearance; drop in Hb level and hospital stay. There were little complications found in patients. But this study showed that mini PCNL is good procedure in treatment of renal calculi.